Navigating through novelties concerning mCRC treatment—the role of immunotherapy, chemotherapy, and targeted therapy in mCRC - Zheng, Edward; Włodarczyk, Marcin; Węgiel, Andrzej; Osielczak, Aleksandra; Możdżan, Maria; Biskup, Laura; Grochowska, Agata; Wołyniak, Maria; Gajewski, Dominik; Porc, Mateusz; Maryńczak, Kasper; Dziki, Łukasz (Frontiers in Surgery, 2024)
Over the course of nearly six decades since the inception of initial trials involving 5-FU in the treatment of mCRC (metastatic colorectal cancer) (McQuade et al., 2017), our progressive comprehension of the pathophysiology, genetics, and surgical techniques related to mCRC has paved the way for the introduction of novel therapeutic modalities. These advancements not only have augmented the overall survival but have also positively impacted the quality of life (QoL) for affected individuals. Despite the remarkable progress made in the last two decades in the development of chemotherapy, immunotherapy, and target therapies, mCRC remains an incurable disease, with a 5-year survival rate of 14%. In this comprehensive review, our primary goal is to present an overview of mCRC treatment methods following the latest guidelines provided by the National Comprehensive Cancer Network (NCCN), the American Society of Clinical Oncology (ASCO), and the American Society of Colon and Rectal Surgeons (ASCRS). Emphasis has been placed on outlining treatment approaches encompassing chemotherapy, immunotherapy, targeted therapy, and surgery's role in managing mCRC. Furthermore, our review delves into prospective avenues for developing new therapies, offering a glimpse into the future of alternative pathways that hold potential for advancing the field.